Exploring the relevance of communication management strategies in resolving communication crises among customer service officers in Malaysia. - Ahmad, Nurbarirah; Tengku Mahamad, Tengku Elena; Tew Abdullah, Muhammad Hakimi; Noranee, Shereen; Sakarj, Siti Rosnita (International Journal of Accounting, Finance and Business, 2025)
This article explores the importance of communication management strategies when dealing with communication crises. Efficient communication management is crucial for achieving employee satisfaction. Organisations must employ communication management strategies to ensure that pertinent information is delivered to the correct individuals in a timely manner. The researcher explores the relevance of communication management strategies in resolving communication crises among customer service officers in Malaysia. This study tends to discover the value of communication management strategies during communication crises in Malaysia. Qualitative methods are employed by utilizing in-depth interviews with employees from various services industries in Malaysia. A total of three employees from the several services industries in Malaysia were chosen as the participants. The ATLAS.ti version 24 programme was used to facilitate data management, and Transcribe Application were used to transcribe data and then utilised to standardise communication management practises. The study's results are expected to establish a model for communication management strategies in the services industry's management of communication crises. Organisations can reduce the adverse impacts of communication crises, like staff stress, anxiety, and low morale, by implementing the Communication Management Strategies Model.